2014
DOI: 10.1016/j.jjcc.2013.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin attenuates pressure overload-induced cardiac hypertrophy

Abstract: Puerarin may have an ability to retard the progression of cardiac hypertrophy and apoptosis which is probably mediated by the blockade of PI3K/Akt and JNK signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 43 publications
(52 reference statements)
4
70
0
1
Order By: Relevance
“…TGF-β also acts as a pro-fibrotic and proapoptotic factor in the heart. 23, 24 Thus, the suppression of TGF-β1 expression caused by GIP might contribute to the prevention of cardiac fibrosis and apoptosis, as well as cardiomyocyte enlargement. In respect to mechanisms in the suppression of TGF-β1 expression by GIP signaling, there are possibilities that nicotinamide adenine dinucleotide phosphate (NADPH) oxidase and p38 mitogen-activated protein kinase (MAPK) are involved.…”
Section: Anti-hypertrophic Effects Of Gip In Wt Micementioning
confidence: 99%
“…TGF-β also acts as a pro-fibrotic and proapoptotic factor in the heart. 23, 24 Thus, the suppression of TGF-β1 expression caused by GIP might contribute to the prevention of cardiac fibrosis and apoptosis, as well as cardiomyocyte enlargement. In respect to mechanisms in the suppression of TGF-β1 expression by GIP signaling, there are possibilities that nicotinamide adenine dinucleotide phosphate (NADPH) oxidase and p38 mitogen-activated protein kinase (MAPK) are involved.…”
Section: Anti-hypertrophic Effects Of Gip In Wt Micementioning
confidence: 99%
“…However, although current pharmacological approaches appear to be beneficial in improving the quality of life of patients with heart failure, they do not markedly reduce the mortality rates (4). A previous study showed that puerarin attenuates the cardiac hypertrophy induced by pressure overload by downregulating phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) and c-Jun N-terminal kinase (JNK) signaling pathways (5). Therefore, a key future challenge is the identification of pharmacological agents that alleviate progressive myocardial dysfunction and unfavorable remodeling, improve the quality of life and reduce the mortality rate of patients with heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…Naringenin is a bitter principle component of grapefruit (Citrus paradisi) that exhibits a variety of pharmacological effects, including anti-inflammatory (6), hypolipidemic, antithrombotic and antiatherogenic properties (5). The dietary consumption of citrus fruits is associated with a reduced rate of acute coronary events (7), and naringenin appears to exert beneficial effects on the cardiovascular system (8).…”
Section: Introductionmentioning
confidence: 99%
“…In adult mice and rat hearts, pressure overload activates several pathways, including the mitogen-activated protein kinase pathway, resulting in hypertrophy and eventually heart failure via remodeling with fibrosis. 8,9) Mechanical stretch on isolated neonatal CMs, directly or indirectly (as in the case of paracrine secretion), induces hypertrophy via the same pathway that induces hypertrophy of adult CMs after constriction. 10) In this neonatal model, the hearts in the constriction group showed increased wall thickness without fibrosis, as well as improved hemodynamics and left ventricular ejection fraction via the CM proliferative response; however, hypertrophy was not observed.…”
Section: Article P264mentioning
confidence: 99%